9PPlasma gene conversions after one cycle (C) abiraterone acetate (AA) for metastatic castration-resistant prostate cancer (mCRPC): A biomarker analysis of a multi-centre, international trial. (7th November 2019) - Jayaram, A K; Shen, D; Wingate, A; Wetterskog, D; Sternberg, C; Jones, R; Berruti, A; Lefresne, F; Lahaye, M; Thomas, S; Joshi, S; Gormley, M; et al.
Abstract: Background: A number of genomic alterations detected in plasma DNA have been associated with worse outcome in mCRPC (Jayaram et al Cancer Discov). We hypothesized that patients (pts) who harbored a genomic alteration that decreased after 1C of treatment derive treatment benefit and this would distinguish them from truly resistant pts. Methods: Plasma DNA (128 C1 day (D) 1, 134 C2 D1, and 41 progression [PD] from chemotherapy-naïve mCRPC pts in a phase 2 study of AA (NCT01867710), recently reported (Attard et al, Jama Onc) were subjected to custom targeted-capture NGS. Assay was optimised and validated to detect pathogenic point mutations (PM), deletions and copy number alterations (CNA) inAR, TP53, RB1, PIK3CA and DNA repair deficient genes (DRD): BRCA1, BRCA2, FANCA, ATM, CHEK2, HDAC2, BRIP1, and PALB2. Pts were followed up for overall survival (OS) and radiographic progression-free survival (rPFS) (48 months). Results: Pts were classified into 4 groups based on whether a gene alteration was detectable (+) or not (-) at C1D1 and C2D1 respectively. At C1D1, 49 pts (37.5%) had + alterations. Pts who converted from + to - (+/-) had similar outcomes as pts who remained - (-/-) and those that did not convert had worst outcomes (+/+) (Table). In matched C1D1 and PD samples pts with ARgain (G) at C1D1 were more ARG at PD (p = <0.01) while ARPM were only detected in PD samples that were ARnormal (N) at C1D1. DRD + pts at C1D1 were more likely DRD + at PD (p = <0.1). Conclusions: These findings suggest that tracking gene aberrations in plasma DNA could be an early marker of treatment efficacy. Clinical trial identification: NCT01867710. Legal entity responsible for the study: The authors. Funding: Janssen Pharmaceuticals. Disclosure: D. Shen: Shareholder / Stockholder / Stock options, Full / Part-time employment: Janssen Research and Development. A. Wingate: Honoraria (self), Research grant / Funding (self), Travel / Accommodation / Expenses: Janssens. C. Sternberg: Honoraria (self): Astellas Pharma; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Honoraria (self), Research grant / Funding (institution): Sanofi; Honoraria (self), Advisory / Consultancy: Ipsen; Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self), Research grant / Funding (institution): Janssen; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy: Novartis; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy: Eisai; Advisory / Consultancy, Research grant / Funding (institution): Clovis Oncology; Advisory / Consultancy, Research grant / Funding (institution): Incyte; Advisory / Consultancy: Roche; Advisory / Consultancy: Ipsen; Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy: Medscape; Advisory / Consultancy: UroToday; Advisory / Consultancy: Genentech; Advisory / Consultancy: Medivation; Research grant / Funding (institution): Exelixis. R. Jones: Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Astellas Pharma; Honoraria (self), Travel / Accommodation / Expenses: Janssen; Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self), Travel / Accommodation / Expenses: MSD Oncology; Honoraria (self): BMS; Honoraria (self), Research grant / Funding (institution): Pfizer; Honoraria (self), Research grant / Funding (institution): Novartis; Honoraria (self), Travel / Accommodation / Expenses: Ipsen; Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Clovis Oncology; Research grant / Funding (institution): Exelixis; Honoraria (self): Sanofi; Honoraria (self): Genentech; Honoraria (self): Eusa Pharma; Honoraria (self): Pharmacyclics. A. Berruti: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Janssen-Cilag; Advisory / Consultancy, Research grant / Funding (institution): Astellas Pharma; Travel / Accommodation / Expenses: Sanofi. F. Lefresne: Honoraria (self), Research grant / Funding (self), Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Full / Part-time employment: Johnson & Johnson. M. Lahaye: Honoraria (self), Advisory / Consultancy, Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment: Janssen-Cilag. S. Thomas: Leadership role, Research grant / Funding (self), Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Licensing / Royalties, Full / Part-time employment: Janssen Research and Development. S. Joshi: Honoraria (self), Travel / Accommodation / Expenses, Full / Part-time employment: Janssen Research and Development. M. Gormley: Travel / Accommodation / Expenses, Licensing / Royalties, Full / Part-time employment: Janssen Research and Development. B. Tombal: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Astellas Pharma; Honoraria (institution), Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Amgen; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Bayer; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Ferring; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Sanofi; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Janssen; Advisory / Consultancy: Takeda; Advisory / Consultancy: Steba Biotech; Honoraria (self): Myovant Sciences. A. Merseburger: Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Janssen-Cilag; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Astellas Pharma; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Ipsen; Honoraria (self): Roche; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): BMS; Honoraria (self): Eisai; Honoraria (self): Takeda; Honoraria (self): Pfizer; Honoraria (self), Research grant / Funding (self): Novartis; Research grant / Funding (institution): Clovis Oncology. D. Ricci: Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Licensing / Royalties, Full / Part-time employment: Janssen. G. Attard: Honoraria (self), Honoraria (institution), Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Janssen; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Astellas Pharma; Advisory / Consultancy: Janssen-Cilag; Research grant / Funding (institution): Innocrin; Research grant / Funding (institution): Arno; Advisory / Consultancy, Travel / Accommodation / Expenses: Ventana Medical Systems; Travel / Accommodation / Expenses: Abbott Laboratories; Licensing / Royalties: ICR Rewards to Inventors; Honoraria (self), Travel / Accommodation / Expenses: Abbott; Advisory / Consultancy, Travel / Accommodation / Expenses: ESSA; Advisory / Consultancy, Travel / Accommodation / Expenses: Bayer; Advisory / Consultancy, Travel / Accommodation / Expenses: Pfizer. All other authors have declared no conflicts of interest.